Corruption dynamics: a mathematical model and analysis - Aga, Beza Zeleke; Tasisa, Hika Gemechu; Keno, Temesgen Duressa; Geleta, Adugna Gadisa; Dinsa, Dechasa Wegi; Geletu, Abebe Regassa (Frontiers in Applied Mathematics and Statistics, 2024)
This work proposes and analyzes a deterministic mathematical model to describe the dynamics of corruption transmission. We began by proving that the solution to the model is bounded and positive. The next-generation matrix approach is used to compute the basic reproduction number (R 0 ) in relation to corruption-free equilibrium.The Jacobian and Lyapunov functions are used to show that corruption-free equilibrium is asymptotically stable in both locally and globally when R 0 < 1 and otherwise, an endemic corruption equilibrium develops. Furthermore, the sensitivity of the model's parameters was investigated. The findings demonstrate that religious precepts govern public education. The two sectors most susceptible to corruption control are education and corrections. The study recommends investing more in the provision of public education to citizens by creating awareness among all and including it in the education curriculum and religious leaders to teach their followers seriously about the impact of corruption as well as the use of jail as punishment. The numerical simulation results agreed with the analytical results.